EXTRACTION, CHARACTERIZATION AND APPLICATION OF CHITOSAN DERIVED FROM MAGGOT (BLACK SOLDIER FLY) WASTE AS EDIBLE COATING FOR RED GRAPES (Vitis vinifera) - Sri Wahyuni; Ranti Selvina; Puspa Julistia Puspita; Haryo Tejo Prakoso; Priyono priyono; Siswanto siswanto (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Black Soldier Fly (BSF) farming showed an increasing trend in the past 5 years. The production process generates a leftover, that is the exuviae which are still untapped. BSF exuviae contain chitin and chitosan which can be utilized in various fields, one of which is fruit preservatives. Grapes (Vitis vinifera) is known to have many benefits and has a content of vitamins A, B, C, and E but it has a short shelf life. The purpose of this study was to characterize chitosan from BSF exuviae and choose the best edible coating method to be applied to grapes to prolong the grape’s storage time. Characterization includes physical condition, percent solubility, degree of deacetylation, and yield of the chitosan. Then, edible coating tests were carried out with 2% acetic acid solvent followed by two different methods, namely dyeing method with 5, 10 and, 15 minutes immersion time and spray method with a chitosan solution concentration of 0,5%, 1%, 1,5%, 2 %, and 2,5%. The results showed that chitosan extracted from BSF exuviae produced a physical appearance in the form of white brown powder with 55% solubility and a degree of deacetylation of 91,88%. The chitin yield is 16,2%, followed by the chitosan yield of 4,8%. The best edible coating method which can maintain the physical appearance of grapes and inhibiting fruit decayed was obtained by dipping method at a concentration of 2,5% for 10 minutes. Based on the overall observations, however, the results obtained from the dip and spray method were not significantly different.